2022
DOI: 10.1186/s12875-022-01743-6
|View full text |Cite
|
Sign up to set email alerts
|

Factors used by general practitioners for referring patients with chronic musculoskeletal pain: a qualitative study

Abstract: Around 20% of the Dutch population is living with chronic musculoskeletal pain (CMP), which is a complex and multifactorial problem. This complexity makes it hard to define a classification system, which results in non-satisfactory referring from the general practitioner (GP). CMP is often explained using the biopsychosocial model in which biological, psychological and social factors cause and maintain the pain. The presented study investigated the factors related to the GPs’ referral for patients with CMP to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Physiotherapists used very brief explanations when reporting contributing factors to chronic pain with a median of 13 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) words. When exploring which themes were most frequently mentioned (Figure 1), approximatively two thirds of the physiotherapists mentioned "Beliefs" or "Emotions" as contributing factors to the pain.…”
Section: How Do Physiotherapists Explain Contributing Factors To Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Physiotherapists used very brief explanations when reporting contributing factors to chronic pain with a median of 13 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) words. When exploring which themes were most frequently mentioned (Figure 1), approximatively two thirds of the physiotherapists mentioned "Beliefs" or "Emotions" as contributing factors to the pain.…”
Section: How Do Physiotherapists Explain Contributing Factors To Painmentioning
confidence: 99%
“…The second step is the identification of unhelpful beliefs, attitudes, emotions, behaviour, social factors, etc., of the patient (i.e., psychosocial factors often referred to as "Yellow Flags"), as these are indicative of poor outcomes [18][19][20][21]. However, research has shown that health care practitioners (HCPs) working in first-line care such as general practitioners and physiotherapists do not sufficiently assess these "Yellow flags" [22][23][24]. Moreover, many HCPs still have biomedical beliefs that pain can be reduced to a degeneration or anomaly of a body structure, independent of psychosocial factors, leading to biomedically-oriented advice restricting the patient in work or activities [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%